(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Irrigation is necessary when it comes to agricultural productivity and growth. For Irrigation,more than 80 percent of water is used all over the world and in India as well. However, the standardamount of water used in India for irrigation projects is evaluated to be around 30-35 percent. Though it isvery certain that rehabilitation of irrigation system is revolutionary and will save water dramatically. Butmodernization and new techniques demands colossal funding expenditure, therefore precarious toendorse and it is necessary to to visualise pioneering, effortless, cheap and sophisticated watertransmission techniques that are being used in few irrigation project in Maharashtra today. The paperdiscusses the need to boost or escalate the water consumption efficiencies of existing irrigation projectsand new project. The input reveal that such progressive techniques will be enforced in other areas ofirrigation projects which will be economically feasible to achieve improvement in crop yield andexcellent water management with high water use efficiency.